2008
DOI: 10.2460/javma.233.9.1420
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the effects of diazepam in dogs with anxiety-related behavior problems

Abstract: Adverse effects of diazepam in dogs were commonly reported and often led to drug discontinuation. Owner education and follow-up is recommended to avoid treatment failure when prescribing diazepam for anxiety-related behavior problems in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 8 publications
4
34
2
1
Order By: Relevance
“…Owner satisfaction and treatment success data. (Crowell-Davis et al, 2003;Cracknell and Mills, 2008;Gruen and Sherman, 2008;Herron et al, 2008;Ibanez and Anzola, 2009;Ogata and Dodman, 2011). One study has shown no statistically significant difference between dogs whose owners interacted with them during a storm and those that did not (Cottam et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Owner satisfaction and treatment success data. (Crowell-Davis et al, 2003;Cracknell and Mills, 2008;Gruen and Sherman, 2008;Herron et al, 2008;Ibanez and Anzola, 2009;Ogata and Dodman, 2011). One study has shown no statistically significant difference between dogs whose owners interacted with them during a storm and those that did not (Cottam et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Psychotropic medications including SSRIs Ibanez and Anzola, 2009), serotonin 2A antagonist/reuptake inhibitors (Gruen and Sherman, 2008), TCAs (Crowell-Davis et al, 2003), alpha-2 agonists (Ogata and Dodman, 2011), and benzodiazepines (Crowell-Davis et al, 2003;Herron et al, 2008;Ibanez and Anzola, 2009) have been studied as treatments for noise phobias and other situational anxieties in dogs. However, daily psychotropic medications including SSRIs and TCAs may have possible obstacles to success including a delayed onset of therapeutic effect of up to 4 weeks (Crowell-Davis and Murray, 2006) and the potential need for an additional situational medication (Crowell-Davis et al, 2003;Gruen and Sherman, 2008;Ibanez and Anzola, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herron et al discussed anxiolytic effects of diazepam through GABA receptors on animal subjects [16]. Taking into account that saffron is traditionally used as anxiolytic medicine and given its effect on lessening anxiety before surgery, the probable cause of such effects are physiologic and biologic effects of the medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since the veterinary literature qualitatively cites case studies of accidental GABA-A receptor modulator and antihistamine ingestion causing paradoxical hyperarousal in healthy dogs (Barnett et al, 1984; Bertini et al, 1995; Richardson et al, 2002; Wismer, 2002; Herron et al, 2008; Lancaster et al, 2011), we quantitatively pre-tested several representative drugs via polysomnography (PSG) to determine whether we could evaluate different pharmacological hypnotic mechanisms in the salience gating arousal paradigm.…”
Section: Introductionmentioning
confidence: 99%